Czech Adaptation of Test 13 Visual-Auditory Learning Included in Woodcock-Johnson IV Tests of Cognitive Abilities - Mrázková, Monika; Furman, Anton; Ťápal, Adam; Urbánek, Tomáš (Studia Psychologica, 2023)
The main goal of this article is to describe the process of adaptation of Test 13: Visual-Auditory Learning, part of the Woodcock-Johnson IV Tests of Cognitive Abilities, to Czech. Specific attention is given to explaining how the authors of the adaptation dealt with the differences of the two languages between which the adaptation occurred. Test 13 is a controlled learning task and consists of Test Stories, in which symbols represent the words. Some of the differences between English and Czech did not allow simple translation of the words, deeper changes were required. The analysis of standardization data set showed an excellent reliability, however, to confirm the validity of the Czech version, further empirical studies are needed. The uniqueness of this article lies on the description of adaptation of the test to the language from the Slavic language group. It can be useful for other researchers from Slavic languages speaking countries.